2018
DOI: 10.2196/10528
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent mHealth Intervention for Large, Sustained Change in Multiple Diet and Activity Risk Behaviors: The Make Better Choices 2 Randomized Controlled Trial

Abstract: BackgroundPrevalent co-occurring poor diet and physical inactivity convey chronic disease risk to the population. Large magnitude behavior change can improve behaviors to recommended levels, but multiple behavior change interventions produce small, poorly maintained effects.ObjectiveThe Make Better Choices 2 trial tested whether a multicomponent intervention integrating mHealth, modest incentives, and remote coaching could sustainably improve diet and activity.MethodsBetween 2012 and 2014, the 9-month randomiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 65 publications
1
103
0
Order By: Relevance
“…In the parent study, both the sequential and simultaneous groups showed comparably large, sustained diet and activity improvements, as described previously [40]. Therefore, we compared the control group to pooled samples from the sequential and simultaneous groups.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…In the parent study, both the sequential and simultaneous groups showed comparably large, sustained diet and activity improvements, as described previously [40]. Therefore, we compared the control group to pooled samples from the sequential and simultaneous groups.…”
Section: Resultsmentioning
confidence: 62%
“…The primary study outcome was sustained improvement from baseline through 9-month follow-up, and the secondary outcomes were improvement in individual diet and activity behaviors. In the original study, sequential and simultaneous interventions produced similar and sustained diet and activity improvement compared to control (p < 0.001), and the effects were comparable between intervention groups [40].…”
Section: Make Better Choices 2 (Mbc2) Study Population and Interventimentioning
confidence: 92%
See 1 more Smart Citation
“…For example, Vandelanotte et al reported that sequential delivery was slightly more effective in producing sustained increases in PA and decreases in fat intake after 2 years. The Make Better Choices 2 Trial , a multicomponent mobile health intervention targeting increases in fruit and vegetable intake and MVPA, produced a composite improvement in diet and PA when interventions were delivered sequentially. However, weight loss was not an outcome in either study.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach, which has not been widely considered, is to deliver diet and exercise interventions sequentially. Delaying the start of an exercise intervention after diet‐induced weight loss could result in enhanced exercise adherence and improved weight loss long term because (1) perceived enjoyment of exercise may be higher at a lower body weight , (2) risk of exercise‐related injuries may be reduced after weight loss , and (3) focusing on one behavioral change at a time may lead to greater long‐term adherence to both diet and exercise behaviors . However, there has been limited evidence regarding the effect of simultaneous versus sequential interventions to improve diet and PA behaviors on weight loss.…”
Section: Introductionmentioning
confidence: 99%